إشكالية النَّص والاجتهاد بالرأي في العصر الحديث: دراسة أصولية تحليلية - رائد نصري أبو مؤنس (International Institute of Islamic Thought, 2019)
يُعَدُّ "منهج التجديد بالاجتهاد بالرأي" من أهم دعوات التجديد في العصر الحديث، والتي التفَّ حولها كبار علماء التشريع الإسلامي وأساتذته. منهج له آراؤه ومواقفه الـمُحدَّدة من قضايا التجديد، وفي مقدمتها العلاقة بين النَّص والاجتهاد بالرأي؛ بما هي قضية مشكلة تحتاج إلى وضع حدود ومعايير ضابطة لها. وقد عرض البحث لأهم مناحي دعوات التجديد في العصر الحديث، وصولاً إلى إبراز منهج الاجتهاد بالرأي، وموقفه من التجديد في النَّص الشرعي مشفوعاً بدراسة أصولية تحليلية. وانتهى البحث إلى أنَّ الاجتهاد بالرأي هو منهج تشريعي مستقر، يقبله النَّص الشرعي، قطعياً كان أم ظنياً، بكيفيات ومعايير مُحدَّدة، تحفظ للنص مكانته ووظيفته، وتُطلِق للاجتهاد آفاقاً ممتدةً. The approach of Ijtihad through opinion is considered one of the most important calls for renewal in modern era. This approach has attracted great scholars of Islamic jurisprudence and university professors. It has its own opinions and positions about issues of renewal, especially the issue of the relationship between the Islamic original text and the Ijtihad through Opinion. This issue requires setting certain conditions and criteria to guarantee needed control. This study have illustrated the most important aspects of the call for renewal in the modern era, that would highlight the approach of Ijtihad through Opinion and its position towards renewal of our understanding of the original Islamic text. In order to do that the study uses a fundamentalist analytical approach. This study has concluded that Ijtihad through opinion is a sound legal approach, accepted by the Islamic text whether our understanding of the text is categorical or just a possible one. However it should be accepted within certain qualities and criteria that preserve the status and function of the text, and open broad prospects for Ijtihad.